PENERAPAN DISCOVERY LEARNING DENGAN ALAT BANTU HITUNG SEDERHANA DALAM PENINGKATAN MINAT DAN HASIL BELAJAR BILANGAN BULAT PADA SISWA KELAS IV SD NEGERI MUKTISARI TAHUN AJARAN 2015/2016 - mulia, Frestika (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Discovery LearningModel Using Simple Counting Tools in Improving Students? Interest and Learning Outcomes about Integers for the Fourth Grade Students of SD Negeri Muktisari in the Academic Year of 2015/2016.The objectives of this research areto improve students? interest and learning outcomes. Subjects of the research were 20 students of the fourth grade of SD Negeri Muktisari. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of two meetings including planning, action, observation, and reflection. Sources of data were derived from students, teacher, and documents. Techniques of collecting data were test, observation, interview, questionnaire, and documentation. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed using quantitative and qualitative descriptive analysis consisting of data reduction, data display, and drawing conclusion or verification.The results of this research showed thatthe application of Discovery Learning method using simple counting tools can improve students? interest and learning outcomes. Keywords:Discovery Learning, simple counting tools, Mathematics Abstrak: Penerapan Discovery Learning dengan Alat Bantu Hitung Sederhana dalam Peningkatan Minat dan Hasil Belajar Bilangan Bulat pada Siswa Kelas IV SD Negeri Muktisari Tahun Ajaran 2015/2016. Tujuan penelitian ini adalah meningkatkan minat dan hasil belajar siswa. Subjek penelitian adalah siswa kelas IV SD Negeri Muktisari yang berjumlah 20 siswa. Penelitian ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Sumber data penelitian adalah siswa, guru, dan dokumen. Teknik pengumpulan data dengan tes, observasi, wawancara, angket, dan dokumentasi. Validitas data menggunakan triangulasi teknik dan sumber data. Analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan model Discovery Learning dengan alat bantu hitung sederhana dapat meningkatkan minat dan hasil belajar siswa. Kata Kunci: Discovery Learning, Alat Bantu Hitung Sederhana, Matematika